ChemInform Abstract: Mn4+ Doped (NH4)2TiF6 and (NH4)2SiF6 Micro‐Crystal Phosphors: Synthesis Through Ion Exchange at Room Temperature and their Photoluminescence Properties. Issue 44 (13th October 2016) - Xi, Luqing; Pan, Yuexiao; Huang, Shaoming; Liu, Guokui
Abstract: In view of a large scale industrial production, the title microcrystalline Mn 4+ ‐doped phosphors are prepared by ion exchange of (NH4 )2 TiF6 or (NH4 )2 SiF6 (commercial products) with KMnO4 or K2 MnF6 in aq.